2018
DOI: 10.1007/s00467-018-4052-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different rituximab regimens on B cell depletion and time to relapse in children with steroid-dependent nephrotic syndrome

Abstract: The initial dose of rituximab impacts time to B cell reconstitution and the probability of relapse. Risk of relapse is also associated with patient characteristics, suggesting that RTX regimen could be modified for each patient to balance efficacy, cost, and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…A few studies have been reported with a rituximab dose of 750 mg/m 2 , but this dose has not clearly been associated with a better response rate than the standard dose of 375 mg/m 2 (37, 95). However, using a lower dose of rituximab (100 mg/m 2 ) has been associated with a shorter duration of B cell depletion, and thus appears to increase the risk of earlier relapse (96).…”
Section: Factors That May Affect the Clinical Response Of Rituximab Imentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have been reported with a rituximab dose of 750 mg/m 2 , but this dose has not clearly been associated with a better response rate than the standard dose of 375 mg/m 2 (37, 95). However, using a lower dose of rituximab (100 mg/m 2 ) has been associated with a shorter duration of B cell depletion, and thus appears to increase the risk of earlier relapse (96).…”
Section: Factors That May Affect the Clinical Response Of Rituximab Imentioning
confidence: 99%
“…They found that there was a good correlation between the rituximab dose and the median time to B cell reconstitution (2.5 vs. 5.0 vs. 6.6 months in Groups 1, 2, and 3, respectively). One-year relapse-free survival rates associated with these treatments were also 50, 59, and 72%, respectively (96). These results suggest direct correlations both between dosing regimens and time to B cell reconstitution, and also between time to B cell reconstitution and relapse-free survival.…”
Section: Biomarkers Of Response To Rituximabmentioning
confidence: 99%
“…15,16,28,42 Higher initial doses may not influence time for B cell reconstitution . 45,46 Though there were reports suggesting that a single dose of rituximab may be ineffective, 47 our observations suggest that additional doses of Rituximab spaced within 1 month of initial doses may not be necessary if there are no target B cells in circulation. Similar observations have been reported by others.…”
Section: Discussionmentioning
confidence: 66%
“…Currently, there is no consensus regarding the use of RTX with optimal initial and maintenance dose protocols. Although there is no strong evidence that lower doses increase the risk of earlier relapses or higher doses are more beneficial, the most preferred dose is 375 mg/m (29,30). In the present study, data were collected from 13 different centers retrospectively, with a dose of 375 mg/m 2 and different dose intervals (weekly or biweekly).…”
Section: Discussionmentioning
confidence: 98%